Novel Pathways for Ameliorating the Fitness Cost of Gentamicin Resistant Small Colony Variants - Vestergaard, Martin; Paulander, Wilhelm; Leng, Bingfeng; Nielsen, Jesper B.; Westh, Henrik T.; Ingmer, Hanne (Frontiers in Microbiology, 2016)
Small colony variants (SCVs) of the human pathogen Staphylococcus aureus are associated with persistent infections. Phenotypically, SCVs are characterized by slow growth and they can arise upon interruption of the electron transport chain that consequently reduce membrane potential and thereby limit uptake of aminoglycosides (e.g. gentamicin). In this study, we have examined the pathways by which the fitness cost of SCVs can be ameliorated. Five gentamicin resistant SCVs derived from S. aureus JE2 were independently selected on agar plates supplemented with gentamicin. The SCVs carried mutations in the menaquinone and hemin biosynthesis pathways, which caused a significant reduction in exponential growth rates relative to wild type (0.59-0.72) and reduced membrane potentials. Fifty independent lineages of the low-fitness, resistant mutants were serially passaged for up to 500 generations with or without sub-lethal concentrations of gentamicin. Amelioration of the fitness cost followed three evolutionary trajectories and was dependent on the initial mutation type (point mutation vs. deletion) and the passage condition (absence or presence gentamicin). For SCVs evolved in the absence of gentamicin, 12 out of 15 lineages derived from SCVs with point mutations acquired intra-codonic suppressor mutations restoring membrane potential, growth rate, gentamicin susceptibility and colony size to wild type levels. For the SCVs carrying deletions, all lineages enhanced fitness independent of membrane potential restoration without alterations in gentamicin resistance levels. By whole genome sequencing, we identified compensatory mutations in genes related to the σB stress response (7 out of 10 lineages). Inactivation of rpoF that encode for the alternative sigma factor SigB (σB) partially restored fitness of SCVs. For all lineages passaged in the presence of gentamicin, fitness compensation via membrane potential restoration was suppressed, however selected for secondary mutations in fusA and SAUSA300_0749. This study is the first to describe fitness compensatory events in SCVs with deletion mutations and adaptation of SCVs to continued exposure to gentamicin